Annealing effects on the sound velocity and internal friction in the superconducting and normal states of the Cu30Zr70 amorphous alloy - Esquinazi, P.; Luzuriaga, J. (American Physical Society, 1988)
Fil: Esquinazi, P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina